2013
DOI: 10.1371/journal.pone.0053597
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Activators Suppress Cervical Cancer Cell Growth through Inhibition of DVL3 Mediated Wnt/β-Catenin Signaling Activity

Abstract: Recent evidence has suggested that AMPK activators may be applied as therapeutic drugs in suppressing cancer cell growth. However, the molecular mechanism of their suppressive function in cancer cells is still unclear. Here we show that AMPK activators impair cervical cancer cell growth through the reduction of DVL3, a positive regulator in Wnt/β-catenin signaling and an oncogenic player in cervical cancer tumorigenesis. By western blot and immunohistochemical analyses, we demonstrated that DVL3 was frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 55 publications
(73 reference statements)
2
64
0
Order By: Relevance
“…Indeed, previous studies reported by our team showed that pharmaceutical AMPK activators such as 5-aminoimidazole-4-carboxamide 1-β-D-ribofuranoside (AICAR) (ATP-dependent) and A23187 (ATP-independent) could be used to suppress cervical cancer cell growth harboring with or without LKB1, an upstream kinase of AMPK [44]. Our group also proposed mechanistic evidence showing that metformin, AICAR, and A23187 suppress cell growth of cervical cancer through reducing AKT/FOXO3a/FOXM1 signaling [47] and DVL3, a positive effector of Wnt/β-catenin signaling cascade, has been shown to be activated constitutively in cervical cancer development [48]. More importantly, our latest study of the molecular mechanism revealed that BME acts as a natural AMPK activator through CaMKKβ signaling in an AMP-independent manner, which in turn represses both mTOR/p70S6K and AKT/ERK/FOXM1 signals in ovarian cancer cells (Fig.…”
Section: Amp-activated Protein Kinase In Human Cancer and Its Signifimentioning
confidence: 93%
“…Indeed, previous studies reported by our team showed that pharmaceutical AMPK activators such as 5-aminoimidazole-4-carboxamide 1-β-D-ribofuranoside (AICAR) (ATP-dependent) and A23187 (ATP-independent) could be used to suppress cervical cancer cell growth harboring with or without LKB1, an upstream kinase of AMPK [44]. Our group also proposed mechanistic evidence showing that metformin, AICAR, and A23187 suppress cell growth of cervical cancer through reducing AKT/FOXO3a/FOXM1 signaling [47] and DVL3, a positive effector of Wnt/β-catenin signaling cascade, has been shown to be activated constitutively in cervical cancer development [48]. More importantly, our latest study of the molecular mechanism revealed that BME acts as a natural AMPK activator through CaMKKβ signaling in an AMP-independent manner, which in turn represses both mTOR/p70S6K and AKT/ERK/FOXM1 signals in ovarian cancer cells (Fig.…”
Section: Amp-activated Protein Kinase In Human Cancer and Its Signifimentioning
confidence: 93%
“…4 Increasing lag to 1 year among individuals living more than 1 year after cancer diagnosis. 5 Increasing lag to 2 year among individuals living more than 2 years after cancer diagnosis. 6 Adjusted model contains all variables in " 1" along with BMI prior to diagnosis (in individuals with BMI available).…”
Section: Cancer Epidemiologymentioning
confidence: 99%
“…1 Preclinical evidence suggests a beneficial role for metformin, a first-line oral anti-diabetic agent, in colorectal cancer progression. [2][3][4] Although not fully elucidated, the potential anti-tumour effects of metformin are thought to be due to inhibition of the mammalian target of rapamycin (mTOR) signalling pathway, resulting in suppression of cellular proliferation 5 tumour cell migration and invasion 6 as well as an increase in apoptosis. 7 Despite mounting preclinical evidence supporting a possible therapeutic role for metformin in colorectal cancer, only two epidemiological studies have evaluated the impact of post-diagnostic metformin exposure on cancer outcomes in colorectal cancer patients with type 2 diabetes.…”
mentioning
confidence: 99%
“…Aspirin is also reported to induce the mitochondria/ caspase-3 apoptotic pathway, which is dependent on the Wnt/b-catenin signaling in mesenchymal stem cells (93). For metformin, it has been reported to inhibit the activation of Wnt/b-catenin signaling in cervical cancer cells (94). Metformin has also been reported to increase the expression of Bambi, a TGF-b decoy receptor, and induce prosurvival Wnt/b-catenin signaling in hepatic stellate cells (95).…”
Section: Wnt/b-catenin Pathwaymentioning
confidence: 99%